2010
DOI: 10.1161/strokeaha.110.597443
|View full text |Cite
|
Sign up to set email alerts
|

Triggers of Ischemic Stroke

Abstract: Background and Purpose-Several studies have suggested that exposure to "triggers," could precipitate the onset of ischemic stroke (IS). We performed a systematic review of the potential triggers of IS. Methods-Two independent reviewers identified studies published between January 1980 and June 2010 from MEDLINE and Embase. Where appropriate, odds ratios (ORs) were combined. Results-A total of 26 studies identified 12 potential triggers. Twenty-two studies used a case-control design, and hazard period durations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
82
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 78 publications
0
82
0
1
Order By: Relevance
“…A likely explanation is that the transient nature of acute infection, most of them being banal upper respiratory tract infections, acts as a temporary risk factor for stroke and extends to have effect on short-term outcome only. 3 Compared with PI, the association between PSI and adverse outcome after stroke is based on much more solid evidence. [16][17][18][19] We confirmed that young age does not protect from the deleterious effects of PSI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A likely explanation is that the transient nature of acute infection, most of them being banal upper respiratory tract infections, acts as a temporary risk factor for stroke and extends to have effect on short-term outcome only. 3 Compared with PI, the association between PSI and adverse outcome after stroke is based on much more solid evidence. [16][17][18][19] We confirmed that young age does not protect from the deleterious effects of PSI.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In some studies, preceding infections (PIs) have been linked particularly to large-vessel and cardioembolic ischemic strokes. 5,6 Also chronic infections, such as bronchial or dental infections, may have a potential to cause inflammation, to promote atherosclerosis, and to increase risk for atherothrombotic stroke.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Alcohol abuse, clinical infection/inflammation, recreational drug abuse, psychological distress, stressful life events, birthday, negative or positive emotions, anger, heavy physical exertion, heavy eating, sudden posture change in response to a startling event have been isolated as potential triggering factors for stroke. 9 In a study conducted in Kerala state of Southern India, key components of the metabolic syndrome and smoking are associated with ischaemic stroke in young adults. These results were similar to that observed in the current study in which High BP was found to be a risk factor for stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Yes Cardiovascular diseases Hypertensive heart disease, ischaemic heart disease, ischaemic stroke, haemorrhagic stroke, atrial fibrillation and flutter, conduction disorders Taylor et al, 2009;Guiraud et al, 2010;Patra et al, 2010;Samokhvalov et al, 2010c;Roerecke & Rehm, 2010a,b, 2012.…”
Section: Health Consequences: Mortality and Morbiditymentioning
confidence: 99%